Computer graphics from scratch : a programmer's introduction to 3D rendering - Gambetta, Gabriel, 1980- (No Starch Press, Inc., 2021)
"An introduction to computer graphics that focuses on raytracing and rasterization. Topics and algorithms are presented without the use of external libraries or APIs and with pseudocode that is not specific to a programming language. Includes links to interactive demonstrations for each algorithm"--